2008
DOI: 10.1038/nature06424
|View full text |Cite
|
Sign up to set email alerts
|

Seismic identification of along-axis hydrothermal flow on the East Pacific Rise

Abstract: Hydrothermal circulation at the axis of mid-ocean ridges affects the chemistry of the lithosphere and overlying ocean, supports chemosynthetic biological communities and is responsible for significant heat transfer from the lithosphere to the ocean. It is commonly thought that flow in these systems is oriented across the ridge axis, with recharge occurring along off-axis faults, but the structure and scale of hydrothermal systems are usually inferred from thermal and geochemical models constrained by the geoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
161
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(173 citation statements)
references
References 30 publications
9
161
2
1
Order By: Relevance
“…18). This result is very different from those of de Martin et al (2007) and Tolstoy et al (2008), who found many microearthquakes related to hydrothermal activity. The difference may be because their OBS network had a wider spacing (about 5 km) than the earlier networks (about 1-5 km), and they examined this possibility by checking the seismicity near an OBS, which was less than 1 km from the Pika site.…”
Section: Hydrothermal Vent Sitescontrasting
confidence: 56%
“…18). This result is very different from those of de Martin et al (2007) and Tolstoy et al (2008), who found many microearthquakes related to hydrothermal activity. The difference may be because their OBS network had a wider spacing (about 5 km) than the earlier networks (about 1-5 km), and they examined this possibility by checking the seismicity near an OBS, which was less than 1 km from the Pika site.…”
Section: Hydrothermal Vent Sitescontrasting
confidence: 56%
“…As oceanic plates spread apart, 3 upwelling mantle beneath the ridge undergoes decompressional melting and transport to a narrow zone of crustal formation. Seismic data shows that at fast spreading ridges a zone of partially molten crust underlies a thin, mostly liquid lens of magma 10 to 100 meters thick situated between approximately 1 and 3 kilometers beneath the seafloor [Detrick et al, 1987;Sinton and Detrick, 1992;Sohn et al, 1998;MacLeod and Yaouancq, 2000;Kelley et al, 2002;Tolstoy et al, 2008]. Replenishment of the magma lens, commonly called the AMC (axial magma chamber) may result in diking events and magmatic eruptions [Germanovich et al, 2011].…”
Section: General Background On Seafloor Hydrothermal Systemsmentioning
confidence: 99%
“…This low porosity suggests that these areas would not involve a lot of fluid, potentially because this area is massive and less fractured. The regions of high resistivity could act as barriers for across-axis hydrothermal circulation, leading to preferential along-axis circulation, similar to the observation at the East Pacific Rise (Tolstoy et al 2008).…”
Section: Discussionmentioning
confidence: 81%
“…This result suggests that fluid estimated at 44-200 C is not replaced by 2 C seawater. Fluid at 44-200 C and at depths of 800-1,500 m may represent a hydrothermal heating zone, one example of which was deduced at the East Pacific Rise (Tolstoy et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation